Reducing traffic congestion level of Dhaka city using policy based algorithm in SUMO - Islam, Khandker Mushfiqul; Ahmed, Shihab Uddin (BRAC University, 2018)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2017.